GAMBARAN KEJADIAN DISMENORE PADA REMAJA PUTRI DI FAKULTAS ILMU KESEHATAN UNIVERSITAS PASIR PENGARAIAN - Andriana; Elvira Junita; Sri Mandalika; Suryani (Fakultas Ilmu Kesehatan, 2021)
Dysmenorrhea is a painful condition that occurs during menstruation that can interfere with activities, causing pain in the lower abdomen, which spreads to the lower back and legs. The incidence of dysmenorrhea is experienced by young women around the world on average. The cause of pain is due to an imbalance of the hormone progesterone in the blood. Several factors triggering the occurrence of dysmenorrhea include the first menstruation at an early age, endocrine factors, psychological disorders, allergic, long menstrual periods, heavy menstrual blood flow, smoking, a history of obesity and alcohol consumption. Efforts to overcome dysmenorrhea can be done by non-pharmacological and pharmacological methods. This study aims to describe the incidence of dysmenorrhea in adolescent girls. This study used a descriptive survey method with a questionnaire that was distributed via google form to 73 students of the Faculty of Health Sciences, Pasir Pengaraian University. The results showed that the average menarche at the age of 13-16 years was 39 people (53.43%), the most experienced dysmenorrhea was 52 people (71.23%), the efforts made to reduce dysmenorrhea with rest were 35 people. (47.95 %) and 38 people (52.05%) who tried to reduce the feeling of dysmenorrhea, respondents used drugs to reduce dysmenorrhea, namely 26 respondents (35.62%). The conclusion of this study is that the average age of menarche for adolescent girl is 13-16 years, the majority experience dysmenorrhea, most of the adolescent girl make efforts to reduce dysmenorrhea pain with non-pharmacological and pharmacological methods.